2019
DOI: 10.1007/s00167-019-05646-5
|View full text |Cite
|
Sign up to set email alerts
|

No effect of tourniquet in primary total knee arthroplasty on muscle strength, functional outcome, patient satisfaction and health status: a randomized clinical trial

Abstract: Purpose Tourniquet use during primary total knee arthroplasty (TKA) may negatively impact the early postoperative functional recovery due to molecular effects of ischaemia. The hypothesis of the present study was that primary TKA without a tourniquet positively influences the postoperative muscle strength, functional outcome, patient satisfaction and health status. Methods The monocentric, randomized, controlled trial included a total of 99 patients scheduled to undergo primary TKA (ClinicalTrials.gov NCT02475… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 39 publications
2
33
0
Order By: Relevance
“…Although various randomized clinical trials have been published, the use of a tourniquet during total knee joint replacement has still been a topic of debate [15][16][17]. There is conflicting evidence regarding the effect of tourniquet use on perioperative blood loss and postoperative function and pain.…”
Section: Discussionmentioning
confidence: 99%
“…Although various randomized clinical trials have been published, the use of a tourniquet during total knee joint replacement has still been a topic of debate [15][16][17]. There is conflicting evidence regarding the effect of tourniquet use on perioperative blood loss and postoperative function and pain.…”
Section: Discussionmentioning
confidence: 99%
“…Jahwar et al have recently shown in a prospective study no difference in functional outcome using or not a tourniquet for primary TKA (16) even with a high pressure of 360 mm Hg. Recovery after TKA is certainly more influenced by all perioperative measures than by the use or not of the tourniquet.…”
Section: Discussionmentioning
confidence: 93%
“…The inflate tourniquet-pressure is directly correlated to the rate of complications (5). It is therefore logical to suppose that decreasing the tourniquet-inflate pressure would decrease these complications, however very few papers have demonstrated this (16,17). Interestingly, lower tourniquet-inflate pressures used nowadays are certainly one of the reasons why recent studies show very different results from previous ones concerning TKA complications.…”
Section: Table Imentioning
confidence: 99%
“…Regarding perioperative blood loss, Jawhar et al also reported reduced intraoperative bleeding with the use of a tourniquet but no difference in total bleeding volume [ 16 ]. They also subsequently reported no difference in functional outcomes and patient-reported outcomes in the same cohort [ 19 ]. However, Hasanain et al reported that the use of a tourniquet reduced total bleeding without postoperative complications [ 20 ].…”
Section: Discussionmentioning
confidence: 99%